2023
DOI: 10.1371/journal.pone.0282144
|View full text |Cite
|
Sign up to set email alerts
|

Digger wasps Microbembex monodonta SAY (Hymenoptera, Crabronidae) rely exclusively on visual cues when pinpointing their nest entrances

Abstract: The ability of insects to navigate and home is crucial to fundamental tasks, such as pollination, parental care, procuring food, and finding mates. Despite recent advances in our understanding of visual homing in insects, it remains unclear exactly how ground-nesting Hymenoptera are able to precisely locate their often inconspicuous or hidden reproductive burrow entrances. Here we show that the ground-nesting wasp Microbembex monodonta locates her hidden burrow entrance with the help of local landmarks, but on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Based on our findings, it is unlikely that olfactory information was involved in the butterflies' spatial learning task, as they were able to target the same feeder even in the absence of sucrose (experiments 2 and 3). This suggests that monarch butterflies identified the feeder based on visual spatial information, which is in line with previous research that showed that insects, such as ants and wasps, rely on visual landmarks during orientation [11,14,66,67] and that olfactory cues play only a role in visually featureless environments, as shown for desert ants [68,69].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Based on our findings, it is unlikely that olfactory information was involved in the butterflies' spatial learning task, as they were able to target the same feeder even in the absence of sucrose (experiments 2 and 3). This suggests that monarch butterflies identified the feeder based on visual spatial information, which is in line with previous research that showed that insects, such as ants and wasps, rely on visual landmarks during orientation [11,14,66,67] and that olfactory cues play only a role in visually featureless environments, as shown for desert ants [68,69].…”
Section: Discussionsupporting
confidence: 91%
“…Here, we demonstrated that non-migratory monarch butterflies could relocate rewarding feeders by learning spatial information of visual landmarks. In line with many studies on hymenopterans [7,8,11,14,64,65], the butterflies' performance can best be explained by learning the spatial arrangement of multiple landmarks, i.e. the feeders.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations